177 The EM Leaders Programme: Lessons Learnt from the COVID 19 Frontline. (16th November 2020) - Baird, Hannah; Somerset, Lara; Lowe, Jonathan; Jones, Malcolm; Brewer, Victoria
Abstract : The COVID-19 pandemic has presented many unforeseen challenges including an adaptive leadership response from all those who work within the healthcare sector. The EM Leaders programme is an innovative pilot programme designed to support Emergency Medicine trainees by instilling leadership skills and knowledge and championing a compassionate workplace culture. Never has this more relevant or needed. In order to do this we endeavoured to capture case studies and examples of leadership on the frontline during this COVID period, through a survey sent out through RCEM. A selection of the respondents were then approached to undertake more detailed semi-structured interviews. A thematic analysis on these interviews and survey results was conducted and the themes aligned to the EMLeaders framework; a framework detailing the required competencies and descriptors for each stage of EM training. Key themes identified have been around the opportunity to understand and develop self, with a particular focus on the importance of wellbeing and self-care. Many respondents talked about the need to do this personally in order to manage their own emotions and stressors. Departments, where compassionate leadership have been highlighted and the impact of this on the staff seen. Notable themes identified are around the development of service to adapt for the COVID pandemic. This has often been at rapid speed and is particularly noticeable for senior trainees and junior consultants who have found themselves stepping up. Various leadership challenges have been identified and recalled including managing conflict and challenging behaviour. Respondents also noted challenges in developing network, service and the ED team due to transactional leadership styles within wider organisations, leading to a feeling of disempowerment, team fragmentation, lack of autonomy for shop floor decision making and a belief of feeling undervalued during a time of intense pressure.